2014
DOI: 10.12816/0019063
|View full text |Cite
|
Sign up to set email alerts
|

National Economic Emancipation and Development Strategy Needs : A Springboard for Nigerian Sustainable Development

Abstract: National Economic Emancipation and Development Strategy (NEEDS) is government response to the fight against poverty, hunger and underdevelopment in Nigeria from the federal level to the local level. This strategy provides a well-articulated blue print that has helped governments drive home their efforts towards sustainable and national development. But, unfortunately, this programme has not thrived the way it was planned; from the federal, state and to the local level, owing to some political, economic and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The results of the study showed that the first hypothesis was rejected, which means that community empowerment does not affect the mobilization of economic resources, which is in line with research conducted by (Jegede et al, 2019) and(McDonald et al, 2014) where in their study it was found that various strategies were carried out in empowering youth in Nigeria but were not successful due to poor policy implementation. In this study, community empowerment on economic resources in the tourist village of Sudaji must be carried out optimally and in a targeted manner as an effort to restore economic conditions and the level of welfare of underprivileged communities.…”
Section: Discussion the Effect Of Community Empowerment On The Mobili...supporting
confidence: 73%
“…The results of the study showed that the first hypothesis was rejected, which means that community empowerment does not affect the mobilization of economic resources, which is in line with research conducted by (Jegede et al, 2019) and(McDonald et al, 2014) where in their study it was found that various strategies were carried out in empowering youth in Nigeria but were not successful due to poor policy implementation. In this study, community empowerment on economic resources in the tourist village of Sudaji must be carried out optimally and in a targeted manner as an effort to restore economic conditions and the level of welfare of underprivileged communities.…”
Section: Discussion the Effect Of Community Empowerment On The Mobili...supporting
confidence: 73%